Kajian Cadangan Karbon Tanah dan Keragaan Vegetasi Mangrove di Tanjung Batu- Sekotong Kabupaten Lombok Barat - Nadia Desya Amanda; Sukartono Sukartono; Zuhdiyah Matienatul Iemaaniah; Sri Tejowulan (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2026)
change mitigation efforts. This study aims to measure soil carbon stocks and analyze the performance of mangrove vegetation in Tanjung Batu, Sekotong District, West Lombok Regency. This study was conducted from August to October 2025 using an experimental method and sampling was carried out using a purposive sampling method with six sample points representing ecosystem conditions. Soil samples were taken at three depths (0–15 cm, 15–30 cm, and 30–45 cm) for analysis of organic C, particle size distribution, bulk density, and porosity. Vegetation analysis was carried out using 10 × 10 m plots to obtain density, dominance, and diversity values. The analysis results showed that the soil organic C content ranged from 1.47% to 7.02%, which increased with increasing soil depth. Soil carbon stocks ranged from 34.92–74.55 tons/ha with an average value of 53.53 tons/ha. The vegetation analysis results showed a diversity value of 0.68, which is considered low because only two species were found, namely Rhizophora stylosa and Avicennia lanata, with a total density of 4,483 trees/ha, with Rhizophora stylosa having a relative dominance value of 56.79%. Overall, the Tanjung Batu mangrove ecosystem has a high soil carbon storage capacity and potential as a carbon sink in coastal areas. Soil depth, vegetation density, soil volume weight, and soil porosity play a role in determining the amount of soil carbon stocks.